2017
DOI: 10.1007/s00223-017-0343-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Collagen Crosslinkers on Dentine: A Literature Review

Abstract: This aim of this review is to explore the current research related to crosslinking agents used on dentine. A systematic search of publications in PubMed and Web of Science databases was performed. Further retrieval was conducted using the search terms of specific names of crosslinkers. Reviews, conference abstracts, dissertation and theses, non-English articles, studies of intrinsic crosslinking of dentine, studies of adhesives without specific crosslinker components, studies of crosslinker applications in oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 94 publications
0
25
0
Order By: Relevance
“…The deeper layer of caries or the caries-affected dentin (CAD) is a remineralizable layer and contains a few cariogenic bacteria. There is evidence reported that, mineral precipitation and distribution within dentin can be affected with the condition of collagen matrix (6,7) . So, dentin biomodification modalities should be directed at the remained bacteria, healing of collagen matrix, and substitution of dissolved minerals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The deeper layer of caries or the caries-affected dentin (CAD) is a remineralizable layer and contains a few cariogenic bacteria. There is evidence reported that, mineral precipitation and distribution within dentin can be affected with the condition of collagen matrix (6,7) . So, dentin biomodification modalities should be directed at the remained bacteria, healing of collagen matrix, and substitution of dissolved minerals.…”
Section: Introductionmentioning
confidence: 99%
“…Potential therapeutic agents that enhance collagen matrix modifications should be regarded to improve the firmness of collagenous component of dentin matrix. Cross-linking agents could enhance the mechanical properties of collagen matrix and its resistance to progression of dentin caries (6)(7)(8) . Another modality to enhance collagen matrix firmness is inactivation of MMPs enzyme in carious dentin (9,10) .…”
Section: Introductionmentioning
confidence: 99%
“…They are among the most studied proteins due to their important functions in mammals, including humans. In addition to their structural function in cartilage and skin formation [ 1 , 2 ], as well as in the biomineralization of hard tissues [ 3 ] including bone [ 4 ] and dentine [ 5 ], collagens are involved in the regulation of diverse cellular functions and processes. During the last 60 years, research into collagens has evolved from the discovery of the structure of collagen [ 6 , 7 ], through studies on its chemistry and biochemistry [ 8 , 9 , 10 ], to present-day applications in cell therapy [ 11 ], biomedicine [ 12 , 13 , 14 ], cosmetics [ 15 ], and the food industry [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Collagen exposure is indispensable for resin hybridization, regardless of the protocol followed—etch and rinse, self-etch, or the so-called extrafibrillar demineralization (Gu, Cai, et al 2019). Chemical modification of the collagen matrix by biomimic crosslinking has been suggested as an additional dentin pretreatment step to protect collagen (Bedran-Russo et al 2014; Cai et al 2018). Chemical biomodification by crosslinking agents such as glutaraldehyde, carbodiimide, proanthocyanidin, epigallocatechin gallate, and riboflavin may enhance the mechanical properties of collagen scaffolds and improve the thermal stability and resistance to enzymatic hydrolysis of demineralized collagen matrix (Bedran-Russo et al 2014; Gu, Shan, et al 2019).…”
Section: Introductionmentioning
confidence: 99%